Early Detection of Hemodynamic Responses Using EEG: A Hybrid EEG-fNIRS Study - Khan, M. Jawad; Ghafoor, Usman; Hong, Keum-Shik (Frontiers in Human Neuroscience, 2018)
Enhanced classification accuracy and a sufficient number of commands are highly demanding in brain computer interfaces (BCIs). For a successful BCI, early detection of brain commands in time is essential. In this paper, we propose a novel classifier using a modified vector phase diagram and the power of electroencephalography (EEG) signal for early prediction of hemodynamic responses. EEG and functional near-infrared spectroscopy (fNIRS) signals for a motor task (thumb tapping) were obtained concurrently. Upon the resting state threshold circle in the vector phase diagram that uses the maximum values of oxy- and deoxy-hemoglobin (∆HbO and ∆HbR) during the resting state, we introduce a secondary (inner) threshold circle using the ∆HbO and ∆HbR magnitudes during the time window of 1 sec where an EEG activity is noticeable. If the trajectory of ∆HbO and ∆HbR touches the resting state threshold circle after passing through the inner circle, this indicates that ∆HbO was increasing and ∆HbR was decreasing (i.e., the start of a hemodynamic response). It takes about 0.5 sec for an fNIRS signal to cross the resting state threshold circle after crossing the EEG-based circle. Thus, an fNIRS-based BCI command can be generated in 1.5 sec. We achieved an improved accuracy of 86.0% using the proposed method in comparison with the 63.8% accuracy obtained using linear discriminant analysis in a window of 0 1.5 sec. Moreover, the active brain locations (identified using the proposed scheme) were spatially specific when a t-map was made after 10 sec of stimulation. These results demonstrate the possibility of enhancing the classification accuracy for a brain-computer interface with a time window of 1.5 sec using the proposed method.